New insights into the phylogeny of the dark-spored Myxomycetes (Amoebozoa: Conosa: Myxogastria: Fuscisporidia) and polyphyly of the genus Stemonitis. Issue 3 (2nd April 2020) - Strelow, Daniel; de Haan, Myriam; Bonkowski, Michael; Fiore-Donno, Anna Maria
Abstract : About a thousand described species of Myxomycetes, colloquially named slime moulds, are present in most terrestrial habitats. Molecular environmental sampling has revealed that a significant proportion of sequences could not be assigned to known species, with some specific groups showing a high hidden diversity. One such group included Stemonitis and allied genera, with only a few closely related reference sequences from known species and many distantly related sequences from environmental sampling. To improve the phylogeny and help define genera in this lineage, we provided nine new small-subunit ribosomal RNA gene sequences of Stemonitis and allied genera, along with microscopy observations. We showed that the genus Stemonitis is polyphyletic, clearly separated into two groups, with the main distinguishing feature being spore ornamentation. The first group included the type species Stemonitis fusca, and was characterized by reticulated spores, while the second contained species with warted spores (e.g. S. flavogenita and S. axifera ) and many undetermined environmental sequences. In addition, we show that the related genera Stemonitopsis, Stemonaria and Symphytocarpus were polyphyletic and that their circumscription was based on inconsistent characteristics. Instead, representatives of these genera clustered into the two clades according to their spore ornamentation. Our study provides a first insight into the genetic diversity of Stemonitis and allied genera, and proposes spore ornamentation as an evolutionary informative feature to distinguish genera in this group.